Effect of culture condition on metabolite using osmac approach produced by endophytic strain (4PL2) / Nor Azizah Mohd Abidi - Mohd Abidi, Nor Azizah (2008)
The study was done to identify the effect of culture condition on metabolite production by fungal strain 4PL2. fungi strain 4PL2 was isolated from plant of Pandanus herbaceous which was collected from Port Dickson, Negeri Sembilan in 2006. the study was performed by growing the pure culture of fungi strain 4PL2 in different media, different strength and different incubation period. The pure culture of 4PL2 was then incubated for 2 weeks, 3 weeks and 4 weeks. Then the myceliums of fungi strain 4PL2 were subjected to extraction process by using ethyl acetate as a solvent. After obtaining the pure extracts, then subjected to antimicrobial assay by using disc diffusion method. Three bacteria and two fungi have been used to assay the extract for antimicrobial activity and the result has been recorded. Consequently, the extract was analyzed using HPLC chromatogram to detect the production of major and minor metabolites for different media, different strength and different incubation period. All the data and information obtained from the observations, weight of extracts, microscopic pictures, antimicrobial test and HPLC chromatograms analysis were collected and recorded.